Pola Komunikasi Hubungan Interpersonal Pengasuh Terhadap Anak Asuh Dalam Meningkatkan Kepercayaan Diri - Virna Yuniar; Didi Permadi; A. Zaini Bisri (Lembaga Pengembangan Kinerja Dosen, 2023)
Children who grow up in orphanages have the same rights as children who are in a family environment. Communication carried out by caregivers to provide motivation to foster children in terms of self-confidence. Based on this, orphanage caregivers need to carry out good communication patterns in increasing the confidence of foster children. The theory used in this study is the theory of social penetration popularized by Irwin Altman and Dalmas Taylor. This theory discusses the development of relationships through 4 stages, namely the orientation stage, the exploratory exchange stage, the affective exchange stage, and the stable exchange stage. This research uses a qualitative approach. Researchers use the constructivist paradigm, where knowledge is the result of human construction. Data collection techniques in this study through direct observation, in-depth interviews and documentation. The results showed that the pattern of communication of caregivers to foster children in increasing self-confidence in the Asyiyah orphanage was a wheel pattern, and a star pattern. The relationship between caregivers and foster children goes through 4 stages, namely the orientation stage, the exploratory exchange stage, the affective exchange stage, and the stable exchange stage. Factors that influence the increase in self-confidence in foster children are environmental factors and educational factors.